2018
DOI: 10.1177/0885066618784264
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Meropenem Extended Versus Intermittent Infusion Dosing Protocol in Critically Ill Patients

Abstract: Extended infusion (EI) administration of β-lactams can improve target attainment in critically ill patients with altered pharmacokinetics/pharmacodynamics. To optimize meropenem dosing in patients with severe sepsis/septic shock, our Antimicrobial Stewardship Program implemented a EI meropenem (EIM) protocol in an 18-bed Medical Intensive Care Unit in March 2014. In this retrospective study, we compared intensive care unit (ICU) mortality and clinical response in patients who received meropenem for ≥7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…1). In these studies, outcomes were reported with mortality, clinical cure, microbiological eradication, length of ICU or hospital stay, duration of mechanical ventilation, the percentage of time that the free antibiotic concentration exceeds the MIC (%fT > MIC) and %fT > 4 × MIC 7‐37 . All eligible trials involved the use of beta‐lactams including piperacillin/tazobactam, ticarcillin‐clavulanate, cefepime, ceftazidime, ceftriaxone, cefoperazone, doripenem, imipenem/cilastatin or meropenem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). In these studies, outcomes were reported with mortality, clinical cure, microbiological eradication, length of ICU or hospital stay, duration of mechanical ventilation, the percentage of time that the free antibiotic concentration exceeds the MIC (%fT > MIC) and %fT > 4 × MIC 7‐37 . All eligible trials involved the use of beta‐lactams including piperacillin/tazobactam, ticarcillin‐clavulanate, cefepime, ceftazidime, ceftriaxone, cefoperazone, doripenem, imipenem/cilastatin or meropenem.…”
Section: Resultsmentioning
confidence: 99%
“…The %fT > MIC might decrease to zero for continuous infusion and may remain at a low‐to‐intermediate level when using prolonged or short‐term infusions. It would be interesting to see whether improved RRs in the comparison of continuous and short‐term infusions would result in lower CrCl values 8,9,17,25 …”
Section: What Is New and Conclusionmentioning
confidence: 99%
“…Augmented renal clearance is a well-known risk factor for target failure in antibiotic dosing [35,45], and a number of published studies have shown that prolonged infusion is a valuable treatment option with respect to target attainment, pathogen eradication, and the reduction of mortality [34,46,47]. Nevertheless, many treating physicians in Germany, where the SmPC does not support prolonged infusion, feel uncomfortable with this type of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the studies included in the meta-analysis are described in Table 1. Among nine total studies, two were RCTs (Lyu et al, 2018;Ammar and Abdalla, 2018), three were quasi-experimental studies (Fahimi et al, 2012;Arnold et al, 2013;Bauer et al, 2013) and four were retrospective cohort studies (Lodise et al, 2007;Lee et al, 2012;Ibrahim et al, 2017;Ahmed et al, 2018). The studies spanned three continents (USA, Asia and Africa).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The conventional II period was 30-60 min and the extended infusion duration was 3-4 h. Five studies used the same total daily doses in both arms. In several studies, the β-lactam doses were adjusted for renal insufficiency (Lodise et al, 2007;Lee et al, 2012;Arnold et al, 2013;Bauer et al, 2013;Ibrahim et al, 2017;Ahmed et al, 2018). None of the studies were funded by pharmaceutical companies.…”
Section: Study Characteristicsmentioning
confidence: 99%